The nature of school bullying : a cross-national perspective (London ; New York : Routledge, 1999)
This book is about: Europe; North America; Pacific Rim; and The developing world.
Keywords: Education; Bullying; Bullying -- Cross-cultural studies; School discipline -- Cross-cultural studies; Aggressiveness (Psychology) in children -- Cross-cultural studies